Enhancing the quality of EAP writing through overt teaching. - Wee, Roselind; Sim, Jacqueline; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
This paper examines how overt teaching is instrumental in reducing subject-verb agreement (SVA) errors of Malaysian EAP learners which in turn improves the quality of their writing. The researchers used overt teaching of these grammatical items, that is, SVA and investigated how this method has significantly benefitted the learners who were second year university students from different cultural and language backgrounds. Data was collected using a pre-test and a post-test. Even though the learners had spent more than a decade learning the English language since their early education, the data collected in the pre-test showed that they made gross SVA errors in their writing. Treatment in the form of overt teaching of SVA was given to the learners, after which the post-test was administered. The comparison of data of the two tests revealed significant improvements in the learners’ usage of SVA which resulted in improved quality of their writing. The major findings on the learners’ grammatical problems especially in SVA and their response to overt teaching prove that overt teaching enhances the quality of EAP writing produced by students.